CCAFS’ influence and reach in promoting CSA - Carneiro, Bia; Resce, Giuliano; Ruscica, Giosuè; Ma, Yixin; Pacillo, Grazia; Läderach, Peter R.D.; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Since its inception, CCAFS has engaged with hundreds of partner institutions, from research centers to government bodies, in order to foster policy and institutional change that enable large-scale Climate Smart Agriculture (CSA) adoption. This Info Note summarizes the findings from two studies that aimed to assess the program’s influence on various dimensions. 1. CCAFS has shifted the debate on climate adaptation among strategic partners, with the program’s ideas having reached nearly 60 million people. 2. The program has also inspired positive change in government policy, with nearly 100 policy wins in just the two years up to 2019. 3. It has built a global community for climate adaption and is a key player within a network of more than 60 thousand entities. 4. CCAFS has sparked public interest in CSA, with Google searches for “Climate Smart Agriculture” consistently increasing every month since the program was inaugurated in 2011. 5. The reach of CCAFS science is growing exponentially, with content from CCAFS projects disseminated across 35 thousand URLs from 10 thousand unique domains from more than 150 countries. 6. CCAFS research in partnership with governments in many countries has contributed to increases in public investment in CSA reaching several billions of dollars. Strategies for accelerating private sector financing are now being pursued that are mobilizing new corporate and impact investor spending in climate adaptation actions and innovative CSA-related blended financing (joint government and private sector) approaches towards more sustainable food systems.